2018
DOI: 10.1177/0960327118816134
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of selenium and nano-selenium on bisphenol-induced reproductive toxicity in male rats

Abstract: Bisphenol A (BPA) is a widespread compound associated with the manufacture of many consumer products. The BPA-induced reproductive toxicity was reported to be mainly attributed to oxidative stress. However, the role of antioxidants usage to decrease the injurious effects of BPA, on male reproductive functions, remains to unveil. The present research is established to evaluate the role of selenium (Se) and its nano form (NSe) as protective agents to alleviate BPA-induced testicular toxicity. Ninety mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 59 publications
(56 reference statements)
6
48
0
Order By: Relevance
“…Similar results were detected by Khalaf et al (2019) where it was reported that BPA exposed group could promote apoptosis of germ cells. Data are analysed by one-way ANOVA followed by post hoc test (LSD), 1 p ≤ .001, 2 p ≤ .01, 3 p ≤ .05.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar results were detected by Khalaf et al (2019) where it was reported that BPA exposed group could promote apoptosis of germ cells. Data are analysed by one-way ANOVA followed by post hoc test (LSD), 1 p ≤ .001, 2 p ≤ .01, 3 p ≤ .05.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results were detected by Khalaf et al (2019) where it was reported that BPA exposed group could promote apoptosis of germ cells.…”
Section: Sperm Concentration (×10 6 Cells/ml) Sperm Motility (%)supporting
confidence: 88%
See 1 more Smart Citation
“…Nano Se played important roles in the enhancement of the antioxidant defense system and scavenging free radicals by increasing activities of both and glutathione Stransferase and Glutathione peroxidase [20,40,58] In the present study, the thickness of the neurocyte cell layers (pyramidal and granule layers) was significantly reduced in the group treated with CPH. This reduction occurred due to the decrease in the neurocyte population owing to the cellular damage (necrosis and/or apoptosis).…”
Section: Discussionmentioning
confidence: 49%
“…Se plays a significant role in antioxidant defense systems and it is important for fertility, growth, and immunity in human and animals [4]. Nano-selenium (NSe) showed high biological efficiency due to its good absorptive ability, high bioavailability, high surface activity and low toxicity comparing to other forms of Se [7]. NSe displays potent effects on upregulation of GPx and induction of glutathione S-transferase which resulted in less oxidative stress [8].…”
Section: Introductionmentioning
confidence: 99%